Analisis Faktor-Faktor Yang Mempengaruhi Loyalitas Relawan Taruna Siaga Bencana (TAGANA) Provinsi Jambi - putra, diyo; Assidiqi; Amandha, Shandy (Brida Provinsi Jambi, 2025)
The purpose of this study was to determine the factors that influence the loyalty of cadets on disaster preparedness (TAGANA) in Jambi Province. The research method used is descriptive method with a quantitative approach. The population in this study were volunteers for disaster preparedness cadets (TAGANA) in Jambi Province. The sample was determined by random sampling method so that the number of samples was 250 people.Data collection techniques used questionnaires and processed with SPSS20. The data analysis method used is multiple linear regression method. The results showed that the social spirit had a positive and significant effect on volunteer loyalty by t count 5,246 > t table 1,651. A comfortable environment and workplace have a positive and significant effect on volunteer loyalty by t count 2.937 <t table 1.651. Effective communication has a positive and significant effect on volunteer loyalty of 9,646 < t table 1,651. The relationship between members within the organization has no effect on the loyalty of volunteers because the t count is 0.849 < t table 1.651. Leadership style has no effect on volunteer loyalty because the t count is 1,291 < t table 1,651. However, social life, relationships with members in the organization, leadership style, comfortable environment and workplace, effective communication have a simultaneous and significant effect on the loyalty of TAGANA volunteers with an F count of 190,339 > F table 2.25